DEVELOPMENT DYNAMIC COMPLIANCE COST MODEL FOR IMPLEMENTATION OF BALLAST WATER MANAGEMENT CONVENTION: SHIPOWNER PERSPECTIVE - Hardiyanto,; Pitana, Trika; Handani, Dhimas Widhi (Journal of Applied Engineering Science, 2023)
The Ballast Water Management Convention (BWMC) regulates ship ballast water management to avoid the spread of aquatic invasive species. The convention requires all ships, including existing ones, to have a Ballast Water Treatment System (BWTS) onboard before September 8, 2024. There are some concerns about the compliance costs of BWMC, especially the additional cost of retrofitting cases. The ship retrofitting cost will depend on various factors, and it can be difficult for a shipowner to determine accurately. The procedure is intricate, and there are many factors to consider, such as the ship's size, BWTS system complexity, and the price of materials and modification level. In this paper, A proposed approach involves expert judgment to capture the effect of multi-stakeholder and estimate the compliance cost. As an essential part of the research methodology, the system dynamics method and life cycle cost are combined to develop a compliance cost model during the ship's lifetime. The simulation model shows that the confidence level of retrofitting costs for each BWTS is more than 94%. Therefore, the model can be used to estimate additional costs. As a result, BWTS type A is the most economical system for small tankers, with an estimated cost of USD 802,860 for the remaining 12 years of the ship's lifetime. Shipowners can use this model as a supporting decision tool to determine which BWTS would be suitable and assist in determining the budget necessary to comply with the BWMC.
Keywords: ballast water treatment, retrofitting, compliance cost, system dynamics, life-cycle cost